Detection Capacity of Helicobacter pylori Infection by Stool Antigen Test Comparing with Rapid Urease Test among Peptic Ulcer Disease Patients - Samad, Khurshida; Chowdhury, Md Nazrul Islam; Ara Begum, Kazi Nishat; Ahmed, Imtiaz; Rupom, Touhid Uddin; Saheduzzaman, Md (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Rapid urease test and stool antigen test are both important diagnostic tools for the detection of Helicobacter pylori infection among peptic ulcer disease patients. Objective: The purpose of the present study was to compare the detection capacity of Helicobacter pylori infection with stool antigen test by comparing with rapid urease test among peptic ulcer disease patients. Methodology: This cross-sectional study was conducted in the Department of Clinical Pathology with the collaboration of Department of Gastroenterology at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from October 2011 to September 2012 for a period of one year. All the clinically suspected Helicobactor pylori infected peptic ulcer patients attending in the Department of Gastroenterology at Bangabandhu Sheikh Mujib Medical University (BSMMU) for upper GI endoscopy were selected as study population. Stool antigen test for Helicobactor pylori specific antigen from stool sample was done with “ABON-One Step Helicobactor pylori antigen test device”. Endoscopy of upper GIT was performed in the Department of Gastroenterology. Biopsy taken during endoscopy for RUT. Rapid urease test (RUT) of endoscopic biopsy was performed. Result: A total 86 patients were recruited for this study. The mean (±SD) age was found 38.53(±10.40) years. Out of 86 patients 76 cases were SAT positive and 10 cases were negative. The sensitivity, specificity, positive predictive values and negative predictive values and accuracy of SAT with RUT are 85.53%, 90.0%, 98.48%, 45.0%, 86.05% respectively. The area under the curve was 0.283 with the lower and upper limits of 95% confidence interval of 0.133 and 0.432. This was statistically significant (p=0.003). Conclusion: In conclusion the stool antigen test is an effective method for the diagnosis of Helicobacter pylori infection. Journal of National Institute of Neurosciences Bangladesh, July 2021, Vol. 7, No. 2, pp. 161-164